Bone Mineral Density and Sports Participation - Maillane-Vanegas, Santiago [UNESP]; Agostinete, Ricardo R. [UNESP]; R. Lynch, Kyle [UNESP]; H. Ito, Igor [UNESP]; Luiz-de-Marco, Rafael [UNESP]; Rodrigues-Junior, Mario A. [UNESP]; Turi-Lynch, Bruna Camilo [UNESP]; A. Fernandes, Rômulo [UNESP] (Elsevier, 2018)
The objective of our study was to identify differences in bone mineral density (BMD) according to different sports among adolescents, as well as to identify assessments of relevant mediators. The sample consisted of 429 adolescents with a mean age of 13.3 ± 1.7 yr. The sports modalities that we evaluated were judo, karate, kung fu, swimming, basketball, and soccer. Nonsports group was composed of 111 adolescents. Bone density was assessed using dual-energy X-ray absorptiometry. Regarding BMD values, female engaged in karate had higher BMD values than girls from the no sports group (p = 0.01). Boys engaged in soccer and karate presented the highest BMD values than all the other groups (p = 0.01). The most relevant mediators were the body mass index and lean soft tissue for boys and girls. Different sports presented different results regarding BMD gains, which were influenced by body mass index and whole-body lean soft tissue.
Keywords: Adolescent; bone; exercise; growth; health